Conductive flash evaporation sheet as well as preparation method and application thereof
By adding carbon-based conductive agent, conductive whiskers and porous silica to the polyolefin fiber material, the conductive flash evaporation sheet is prepared by using flash spinning technology, which solves the problem of poor conductivity, and achieves the combination of low resistivity, high breathability and good mechanical properties, which is suitable for battery diffusion layers.
Patent Information
- Application Number
- CN202411939245.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the prior art, after conductivity modification, the conductivity of the polyolefin fiber material does not improve much, and its breathability and mechanical properties decrease, which cannot meet the requirements of the gas diffusion layer.
High-density polyethylene is used as the matrix, carbon-based conductive agent, conductive whiskers and porous silica are added, and conductive flash evaporation sheets are prepared through flash spinning process to build a stable conductive network to improve conductivity and breathability.
It realizes the low resistivity and high breathability of conductive flash evaporation sheets, while maintaining good mechanical properties, and is suitable for the battery diffusion layer.
Smart Images

Figure BDA0005212222710000101 
Figure BDA0005212222710000102 
Figure BDA0005212222710000111
Abstract
Description
Technical Field
[0001] The present application belongs to the field of flash spinning, and specifically relates to a conductive flash spinning sheet and a preparation method and application thereof. Background Art
[0002] The membrane electrode electrolyzer is one of the most promising electrolysis systems, as it electrocatalytically reduces carbon dioxide to carbon monoxide, formic acid, ethanol, ethylene, acetic acid and other carbon-based fuel chemicals at a certain current density. The key components of the membrane electrode electrolyzer include a gas diffusion electrode composed of an electrode gas diffusion layer (GDE) and a catalyst layer. During the electrolysis process, the flowing CO2 gas contacts the electrolyte and the catalyst layer through the electrode gas diffusion layer, thus forming a three-phase interface, which provides a place for the reaction to occur. Therefore, the gas diffusion layer needs to simultaneously meet the moderate contact between the reaction gas, the catalytic active sites and water. This requires the gas diffusion layer to maintain the effective transfer of substances such as reaction gas and water in the gas diffusion layer. The gas diffusion layer needs to have certain hydrophobicity, air permeability, conductivity and provide a certain support strength.
[0003] At present, carbon paper is mostly used as a gas diffusion layer. Carbon paper is a composite material made of carbon fiber as raw material. Carbon paper is light in weight, has a smooth surface, is corrosion-resistant, has uniform porosity and high conductivity, making it widely used in fuel cells, lithium batteries, electrocatalysis and other fields. The catalyst solution or slurry is coated on the surface of the carbon paper to form a catalytic layer, and the coated carbon paper is used as part of the membrane electrode and assembled with other components to form a complete electrochemical reaction system. Carbon paper is usually made of chopped carbon fiber, has a fiber porous structure, and exhibits obvious hydrophilicity. It needs to be hydrophobically modified before use, such as polytetrafluoroethylene modification. The modified carbon paper can establish an effective channel for the conduction of gas and water. However, after the hydrophobically modified carbon paper works in an electric field environment for a period of time, the hydrophobic layer will still be destroyed, and it will not be able to continue to perform its specific functions, resulting in the scrapping of the battery and reducing the service life of the battery. In addition, the process of hydrophobic modification is complicated and the conditions are harsh, resulting in a significant increase in the price of hydrophobically modified carbon paper, which is not conducive to reducing costs and expanding production.
[0004] Polyolefin fiber materials, such as high-density polyethylene, are not only cheap, simple in production process, but also have good hydrophobicity and certain air permeability. If they can replace carbon paper as a gas diffusion layer, their production difficulty and cost can be significantly reduced. However, polyolefin fiber materials are insulating materials and need to be first modified for conductivity to reduce their resistance. The conventional method is to add a conductive agent to the polyolefin material so that it builds a conductive network inside the material, so that it has a certain conductivity and reduces its resistance. However, polyolefin composite materials currently doped with conductive materials such as carbon black, graphene, carbon fiber, metal, etc., due to the dispersibility, compatibility, size, structure, oxidation deterioration, stability and other reasons of the conductive material, it is impossible to build an effective conductive network with the polymer, which not only makes the air permeability and mechanical properties of polyolefin fiber materials significantly reduced, but also the degree of conductivity improvement is not large, and the requirements of the actual gas diffusion layer cannot be met. Summary of the invention
[0005] In view of the problem that the conductive polyolefin fiber materials in the prior art have poor conductivity, the purpose of the present application is to provide a conductive flash-evaporated sheet material and a preparation method and application thereof.
[0006] To achieve the above purpose, the following technical solutions are specifically included:
[0007] A conductive flash-evaporated sheet material comprises the following components in parts by weight: 100 parts of high-density polyethylene, 4-20 parts of carbon-based conductive agent, 3-10 parts of conductive whiskers, 5-15 parts of porous silicon dioxide, 1-5 parts of polyvinyl alcohol, 1-5 parts of compatibilizer, and 0-2 parts of auxiliary agent. The conductive whiskers include zinc oxide whiskers and conductive potassium titanate whiskers. The resistivity of the conductive flash-evaporated sheet material is less than or equal to 200 mΩ·cm, and the compactness of the conductive flash-evaporated sheet material is greater than or equal to 0.4 g / cm 3 And less than or equal to 0.5g / cm 3 .
[0008] The flash nonwoven fabric of the present application is produced by a flash spinning process, which is a spinning method in which a high-density polyethylene matrix spinning solution is extruded into a normal pressure environment under high pressure above the boiling point of the solvent. Due to the sharp drop in pressure, the solvent of the spinning solution evaporates rapidly and is converted into extremely fine fiber filaments, which are then separated, collected, sorted, and reinforced to obtain a flash nonwoven fabric product. Compared with traditional nonwoven fabric materials, flash nonwoven fabrics not only have fine and uniform fiber filaments, but also have high molding efficiency and short production cycle, which is conducive to the subsequent production of a diffusion layer with a small thickness.
[0009] In the conductive flash-steamed sheet of the present application, the carbon-based conductive agent present provides the main conductive function, reduces the resistance of the flash-steamed non-woven fabric, and the conductive whiskers and porous silica assist the conductive agent in building a conductive network, wherein the zinc oxide whiskers with a special four-needle spatial stereoscopic structure and the fibrous conductive potassium titanate whiskers constitute the main skeleton structure, and the porous silica and the conductive agent are interspersed in the skeleton structure, which can not only significantly improve the conductive performance of the system, but also will not significantly reduce the mechanical properties of the system. At the same time, the presence of porous silica provides more pore structures and improves the air permeability of the system. Polyvinyl alcohol can increase the surface wettability of porous silica, zinc oxide whiskers and conductive potassium titanate whiskers, not only improves the porous silica, zinc oxide whiskers and conductive potassium titanate whiskers and polymer matrix better blending, improves the uniformity of the system, improves the dispersibility of the conductive agent, conductive whiskers and porous silica, and can improve hydrophobicity to a certain extent. In addition, the compatibilizer can significantly improve the compatibility between the components, avoiding the decrease in the mechanical properties of the system caused by the addition of porous silica, zinc oxide whiskers and conductive potassium titanate whiskers. Therefore, the conductive flash-evaporated sheet of the present application is based on carbon-based conductive agents, conductive whiskers, porous silica, polyvinyl alcohol and compatibilizers, which can take into account good conductivity, air permeability and mechanical properties, and is more suitable for use in battery diffusion layers.
[0010] Preferably, the average particle size of the porous silica is greater than or equal to 0.01 μm and less than or equal to 3 μm. Further preferably, the average particle size of the porous silica is greater than or equal to 1 μm and less than or equal to 2 μm. The average particle size of the porous silica can specifically be a range value of one or any two of 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, and 3 μm.
[0011] The average particle size of porous silica affects the contact distance and area between it and the conductive agent and conductive whisker. In the nanoscale range, the contact distance between porous silica and the conductive agent and conductive whisker is longer and the contact area is smaller. When the average particle size of porous silica is greater than or equal to 1 μm and less than or equal to 2 μm, the contact distance between porous silica and the conductive agent and conductive whisker is shorter and the contact area is larger.
[0012] Preferably, the specific surface area of the porous silica is greater than or equal to 100 m 2 / g and less than or equal to 1500m 2 / g. The presence of mesopores and micropores on porous silica can significantly improve the air permeability of the system, and the high specific surface area is more conducive to the adsorption of reaction gases, reducing the transmission resistance of gases and other substances, and promoting material transmission.
[0013] The average particle size of the porous silica can be measured by a laser method, and the specific surface area of the porous silica can be obtained by a BET test.
[0014] Preferably, the mass ratio of zinc oxide whiskers to conductive potassium titanate whiskers is (1-12):1, and more preferably, the mass ratio of zinc oxide whiskers to conductive potassium titanate whiskers is (3-11):1. Zinc oxide whiskers and conductive potassium titanate whiskers serve as the skeleton of the conductive network. Their own special morphological structures are conducive to enhancing the toughness and strength of the system, and they have good electrical conductivity, providing a more favorable conductive channel for the conductive agent. At the same time, it is found that when the amount of zinc oxide whiskers is higher than that of conductive potassium titanate whiskers, it is more conducive to improving the conductivity of the system.
[0015] Preferably, the average diameter of the zinc oxide whisker is greater than or equal to 0.5 μm and less than or equal to 5 μm, and the average length is greater than or equal to 10 μm and less than or equal to 50 μm, such as the average diameter can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or any two of the range values, such as the specific average length can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or any two of the range values. The size of conventional commercially available zinc oxide whiskers can meet the requirements of the conductive flash evaporated sheet of the present application.
[0016] Preferably, the average diameter of the conductive potassium titanate whiskers is greater than or equal to 0.05 μm and less than or equal to 5 μm, and the average length is greater than or equal to 0.8 μm and less than or equal to 30 μm. Further preferably, the average diameter of the conductive potassium titanate whiskers is greater than or equal to 0.1 μm and less than or equal to 0.5 μm, and the average length is greater than or equal to 3 μm and less than or equal to 15 μm. For example, its average diameter can specifically be one of the range values of 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm, or any two of the range values. For example, its specific average length can be one of the range values of 0.8 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, and 30 μm, or any two of the range values.
[0017] Potassium titanate whiskers are not conductive in themselves, but can be simply modified to be conductive, and coated or loaded with conductive materials to make them conductive. This not only makes them conductive, but also maintains their own special fibrous morphology and good dispersibility, avoiding agglomeration in the polymer matrix, making them better dispersed in the system, and cooperating with zinc oxide whiskers to improve the conductivity of the system. The diameter and length of potassium titanate whiskers are too small, which is not conducive to their contact with conductive agents, zinc oxide whiskers, etc., and their diameter and length are too large, easy to break, unable to maintain their morphology stable, and not conducive to cooperation with zinc oxide whiskers. Therefore, it is further preferred that the average diameter is greater than or equal to 0.1μm and less than or equal to 0.5μm, and the average length is greater than or equal to 3μm and less than or equal to 15μm. Conductive potassium titanate whiskers are more conducive to improving the conductivity and mechanical properties of the system.
[0018] The diameter and length of zinc oxide whiskers and conductive potassium titanate whiskers can be obtained by scanning electron microscopy.
[0019] More preferably, the conductive potassium titanate whiskers are antimony tin oxide modified potassium titanate whiskers.
[0020] The conductivity modification of potassium titanate whiskers can be carried out by conventional modification methods, such as antimony tin oxide doping modification. The preparation method of antimony tin oxide modified potassium titanate whiskers comprises the following steps:
[0021] (1) Stir tin chloride, antimony chloride, ethanol and acetylacetone to obtain a precursor solution.
[0022] (2) Stir and disperse potassium titanate whiskers in water to obtain a suspension. Add the precursor solution to the suspension and react at 80-95°C for 1.5-6h, then heat to 100-120°C and stir until the solvent evaporates completely to obtain a precursor product.
[0023] (3) The precursor product is calcined at 450-600° C. for 0.5-4 h to obtain conductive potassium titanate whiskers.
[0024] Preferably, in steps (1)-(2), the mass ratio of tin chloride, antimony chloride, acetylacetone, anhydrous ethanol, potassium titanate whisker and water is 0.5-1:0.5-1:0.1-0.3:20-50:3-5:40-60.
[0025] Preferably, in step (1), the reaction time is greater than or equal to 1 h and less than or equal to 3 h.
[0026] Preferably, in step (2), the temperature of the stirring and dispersing is greater than or equal to 50°C and less than or equal to 65°C.
[0027] Preferably, the molecular weight of polyvinyl alcohol (PVA) is greater than or equal to 25,000 and less than or equal to 300,000, and more preferably, the molecular weight of polyvinyl alcohol (PVA) is greater than or equal to 80,000 and less than or equal to 130,000. Conventional commercially available polyvinyl alcohol can meet the requirements of the flash non-woven fabric of this application. Preferably, low molecular weight polyvinyl alcohol is more conducive to the wetting and dispersion of conductive whiskers and silicon dioxide, and improves the uniformity of the system.
[0028] Preferably, the compatibilizer includes at least one of POE-g-MAH (ethylene-octene copolymer grafted with maleic anhydride), PE-g-MAH (polyethylene grafted with maleic anhydride), and LLDPE-g-MAH (linear low density polyethylene grafted with maleic acid).
[0029] The polarity of the compatibilizer grafted with maleic anhydride is greater, which is not only conducive to the adsorption of gas, but also more conducive to improving the compatibility of the polymer matrix with the conductive whisker and porous silica, improving its blending effect, and increasing the uniformity of the system to achieve the purpose of improving conductivity and mechanical properties. Compared with other types of compatibilizers, LLDPE-g-MAH is more compatible with LDPE. Therefore, LLDPE-g-MAH is more effective as a compatibilizer and improves conductivity and mechanical strength to a greater extent. In addition, there are no special requirements for the source and brand of the compatibilizer, which can be homemade or purchased on the market.
[0030] Preferably, the high density polyethylene (HDPE) has a melt index of 5 g / 10 min or more and 15 g / 10 min or less at 190° C. and 2.16 kg load according to ASTM D1238.
[0031] Further preferably, the melt index of the high density polyethylene at 190°C and 2.16 kg load according to ASTM D1238 is one of or any two of 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min, 9 g / 10 min, 10 g / 10 min, 11 g / 10 min, 12 g / 10 min, 13 g / 10 min, 14 g / 10 min, and 15 g / 10 min.
[0032] There are no special requirements for the source and brand of high-density polyethylene raw materials. It can be homemade or purchased on the market. For example, MH602 HDPE purchased on the market can be used, and other types of raw materials can also be used.
[0033] Preferably, the carbon-based conductive agent includes at least one of graphene, conductive carbon black and carbon fiber.
[0034] Further preferably, the average thickness of the graphene layer is greater than or equal to 0.2 mm and less than or equal to 0.5 mm, and specifically can be a range value of one or any two of 0.2 mm, 0.3 mm, 0.4 mm, and 0.5 mm.
[0035] Further preferably, the average length of the carbon fiber is greater than or equal to 0.1 mm and less than or equal to 1 mm, and specifically can be a range value of one or any two of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm.
[0036] Carbon-based conductive agents are light in weight, have good conductivity, and are easy to form a conductive network with other conductive components. In particular, fibrous carbon fibers can significantly shorten the contact distance between conductive components, thereby improving conductive properties and conductive stability.
[0037] Preferably, the auxiliary agent includes at least one of an antioxidant, a lubricant, and a flame retardant.
[0038] Further preferably, the antioxidant includes at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), tris[2.4-di-tert-butylphenyl]phosphite (antioxidant 168), and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecanol (antioxidant 1076).
[0039] Adding other additives can further improve the comprehensive properties of the flash-spun nonwoven fabric. Other additives may optionally include oxidants, lubricants, flame retardants, and the like.
[0040] Preferably, the thickness of the conductive flash-evaporated sheet is greater than or equal to 0.1 mm and less than or equal to 0.2 mm, and further preferably, the thickness of the conductive flash-evaporated sheet is greater than or equal to 0.11 mm and less than or equal to 0.13 mm. A thinner conductive flash-evaporated sheet is more conducive to reducing the transmission resistance of its reaction substances. Moreover, because the conductive flash-evaporated sheet of the present application can still maintain relatively good flexibility and sufficient mechanical properties at a smaller thickness, it can meet the actual application requirements of the battery diffusion layer.
[0041] Preferably, the longitudinal breaking strength of the conductive flash vaporized sheet tested in accordance with GB / T 24218.3-2010 is greater than or equal to 240 N / 5 cm and less than or equal to 253 N / 5 cm, and the transverse breaking strength is greater than or equal to 250 N / 5 cm and less than or equal to 266 N / 5 cm.
[0042] Preferably, the air permeability of the conductive flash-evaporated sheet tested in accordance with GB / T 5453-1997 is greater than or equal to 30 mm / s and less than or equal to 38 mm / s.
[0043] Preferably, the conductive flash sheet has a vertical resistivity greater than or equal to 60 mΩ·cm and less than or equal to 199 mΩ·cm when tested with reference to GB / T20042.7 Proton Exchange Membrane Fuel Cell.
[0044] Preferably, the density of the conductive flash-evaporated sheet is greater than or equal to 0.45 g / cm 3 And less than or equal to 0.48g / cm 3 .
[0045] A method for preparing a conductive flash evaporated sheet comprises the following steps:
[0046] (1) The raw materials are blended, extruded and granulated to obtain masterbatch.
[0047] (2) mixing the masterbatch and the solvent, and then heating and introducing nitrogen so that the temperature in the mixing device is greater than or equal to 200° C. and less than or equal to 230° C., and the pressure is greater than or equal to 10 MPa and less than or equal to 12 MPa, to obtain a spinning solution.
[0048] (3) The spinning solution is subjected to flash spinning, cold pressing, and hot rolling to obtain a conductive flash sheet.
[0049] Preferably, the boiling point of the solvent is less than or equal to 100°C.
[0050] More preferably, the solvent includes at least one of benzene, toluene, butane, pentene, n-hexane, heptane, octane, cyclohexane, dichloromethane, carbon tetrachloride, chloroform, chloromethane, chlorofluoromethane, and ethyl chloride.
[0051] More preferably, the mass ratio of the solid phase to the liquid phase in the spinning solution is (10:90) to (30:70).
[0052] The present application also provides an application of a conductive flash evaporated sheet in the preparation of a gas diffusion layer of a battery, wherein the gas diffusion layer of the battery includes a gas diffusion layer of an electrolytic cell for electrocatalytic reduction of carbon dioxide. The conductive flash evaporated sheet of the present application has a small thickness, low resistance, small diffusion resistance, high air permeability, excellent hydrophobicity, and high tear strength. It can provide sufficient supporting strength for the combination of the catalyst layer and other battery components, is not easy to tear, and has a long service life, thereby providing a scientific and feasible solution for promoting the replacement of carbon paper as a battery diffusion layer.
[0053] Compared with the prior art, the present application has the following beneficial effects: the present application provides the main conductivity for the flash-steamed non-woven fabric by adding a carbon-based conductive agent, and at the same time compounding conductive whiskers and porous silica to form a stable and effective conductive network structure, which significantly reduces the resistance of the flash-steamed non-woven fabric. The dispersibility of the carbon-based conductive agent and the conductive whiskers is improved by polyvinyl alcohol and a compatibilizer, thereby comprehensively achieving the improvement of the conductivity of the flash-steamed non-woven fabric while maintaining the good mechanical properties and high air permeability of the flash-steamed non-woven fabric. DETAILED DESCRIPTION
[0054] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application, unless otherwise specified, are all commonly used ordinary reagents and instruments, which can be purchased on the market, such as the corresponding raw materials purchased from Qilu Petrochemical, Hangzhou Jikang New Materials Co., Ltd., Nantong Aoxin Electronic Technology Co., Ltd., Merck, Sigma-Aldrich, Dongguan Shengli New Materials Co., Ltd. and other companies, and raw materials with corresponding characteristics from other companies can also be used, and there are no special requirements for the grades of the corresponding raw materials.
[0055] Some of the raw materials used in the following examples and comparative examples are described:
[0056] HDPE: The melt index at 190°C and 2.16 kg load is 6 g / 10 min.
[0057] Four-needle zinc oxide whiskers: diameter 0.5-5μm, length 10-50μm.
[0058] Potassium titanate whiskers 1: average diameter 50-100nm, average length 1μm.
[0059] Potassium titanate whiskers 2: average diameter 0.1-0.3 μm, average length 3-5 μm.
[0060] Potassium titanate whiskers 3: average diameter 0.2-0.5 μm, average length 5-15 μm.
[0061] Potassium titanate whiskers 4: average diameter 3-5 μm, average length 10-30 μm.
[0062] Conductive potassium titanate whiskers 1 to 4 are homemade, comprising the following steps:
[0063] (1) 0.8 parts by weight of tin chloride, 0.8 parts by weight of antimony chloride, 40 parts by weight of ethanol and 0.2 parts by weight of acetylacetone were mixed and stirred for reaction for 1.5 hours to obtain a precursor solution.
[0064] (2) 4 parts by weight of potassium titanate whiskers 1 to 4 were stirred and dispersed in 50 parts by weight of water at 60° C. to obtain 4 suspensions. The precursor solution was added to the 4 suspensions respectively, and reacted at 90° C. for 2 h, then heated to 110° C. and stirred until the solvent was completely evaporated to obtain a precursor product.
[0065] (3) The precursor products were calcined at 500° C. for 3 h to obtain conductive potassium titanate whiskers 1 to 4, respectively.
[0066] Porous silica 1: surface area 590-690m 2 / g, average particle size 20nm.
[0067] Porous silica 2: surface area 900-1100m 2 / g, average particle size 1μm.
[0068] Porous silica 3: surface area 300-400m 2 / g, average particle size 2μm.
[0069] Porous silica 4: surface area 300-400m 2 / g, average particle size 3μm.
[0070] Polyvinyl alcohol (PVA): Mw89000-98000.
[0071] Compatibilizer 1: ethylene-octene copolymer grafted with maleic anhydride (POE-g-MAH).
[0072] Compatibilizer 2: linear low density polyethylene grafted with maleic anhydride (LLDPE-g-MAH).
[0073] Graphene: Sheet thickness 0.2-0.5 mm, commercially available.
[0074] Carbon fiber: 0.5-1 mm in length, commercially available.
[0075] The composite antioxidant is obtained by mixing antioxidant 1010 and antioxidant 168 in a 1:1 ratio, and both antioxidant 1010 and antioxidant 168 are commercially available.
[0076] Example 1
[0077] A conductive flash-steamed sheet, the composition of the flash-steamed nonwoven fabric is shown in Table 1, and the specific preparation method comprises the following steps:
[0078] (1) High-density polyethylene, carbon-based conductive agent, conductive whisker, porous silica, polyvinyl alcohol, compatibilizer and optional additives are uniformly mixed in a mixer, and then transferred into a twin-screw extruder for melt extrusion and granulation at 90-180° C. to obtain masterbatch. The temperature of the twin-screw extruder is set as follows: 90-110° C. in zone 1, 120-130° C. in zone 2, 150-160° C. in zone 3, 170-180° C. in zone 4, 170-185° C. in zone 5, 170-185° C. in zone 6, 160-165° C. in zone 7, 160-165° C. in zone 8, 160-165° C. in zone 9, and 160-165° C. in zone 10. The screw speed of the twin-screw extruder is 180-220 rpm.
[0079] (3) The masterbatch was transferred to a reactor containing a mixed solvent of difluorochloromethane and tetrafluorodichloroethane (the volume ratio of difluorochloromethane to tetrafluorodichloroethane was 15:85), preheated to 180°C, then nitrogen was introduced and pressurized to 12 MPa, and finally the temperature was raised to 225°C and stirred in a closed manner for 2 hours. After the temperature stabilized, a spinning solution was obtained, and the mass ratio of the solid phase to the liquid phase in the spinning solution was 15:85.
[0080] (4) Referring to CN115323628B, a flash spinning device 300 or other conventional spinning devices may be used to transfer the spinning solution to the nozzle for spray spinning, and then the spinning solution is refracted and reflected by a rotating filament separator to form a mesh and laid on a moving mesh curtain. The speed of the ejected air flow is 12000 m / min, the frequency of the rotating filament separator is 35 Hz, and the forward speed of the moving mesh curtain is 45 m / min. The collected mesh is cold pressed at a pressure of 0.5 to 1 MPa and hot rolled at a pressure of 140°C and 3 to 3.5 MPa (the hot rolling roller surface speed is 45 to 50 m / min) to obtain a conductive flash sheet.
[0081] Embodiments 2 to 12
[0082] The conductive flash evaporated sheets of Examples 2 to 12 are different from those of Example 1 in that the components of the raw materials are shown in Table 1, and the specific preparation method is the same as that of Example 1.
[0083] Comparative Examples 1 to 6
[0084] The conductive flash-evaporated sheets of Comparative Examples 1 to 6 are different from those of Example 1 in that the components of the raw materials are shown in Table 2, and the specific preparation method is the same as that of Example 1.
[0085] Table 1
[0086]
[0087] Table 2
[0088]
[0089]
[0090] In order to verify the performance of the conductive flash evaporated sheet of the present application, the products prepared in the above embodiments and comparative examples were subjected to the following performance tests, and the specific methods and qualified standards are as follows:
[0091] (1) Breaking strength: Tested in accordance with GB / T 24218.3. Acceptable standard: MD (longitudinal direction) greater than or equal to 240 N / 5 cm, CD (transverse direction) greater than or equal to 250 N / 5 cm.
[0092] (2) Air permeability: Tested in accordance with GB / T 5453, an air permeability greater than or equal to 30 mm / s is considered qualified.
[0093] (3) Resistivity: refer to GB / T20042.7 Proton Exchange Membrane Fuel Cell Part 7: Carbon Paper Characteristics Test Method (Vertical Resistivity), the resistivity is less than or equal to 200 mΩ·cm.
[0094] (4) Sheet tightness: Sheet tightness (g / cm 3 ) = sheet mass (g / m 2 ) / sheet thickness (μm)Qualified standard: Tightness greater than or equal to 0.4 and less than or equal to 0.5g / m 3 .
[0095] The above performance results are shown in Table 3 below.
[0096] Table 3
[0097]
[0098]
[0099] It can be seen from Table 3 that the conductive flash-steamed sheet obtained in the above embodiment has a breaking strength of MD (longitudinal) greater than or equal to 240N / 5cm, and CD (transverse) greater than or equal to 250N / 5cm. The air permeability of the conductive flash-steamed sheet obtained in the above embodiment is greater than or equal to 30mm / s. The resistivity of conventional carbon paper is related to its thickness, and the same is true for the conductive flash-steamed sheet. However, since its thickness has a certain correlation with the gram weight of the flash-steamed non-woven fabric, the relationship between gram weight and thickness is also taken into consideration when preparing or selecting the conductive flash-steamed sheet. Therefore, this application uses tightness to consider the gram weight and thickness of the sheet. When the tightness is 0.4-0.5g / cm 3 Under the condition, the resistivity is less than or equal to 200 mΩ·cm. The conductive flash evaporated sheet of the present application has high air permeability and conductivity while maintaining excellent mechanical properties.
[0100] It can be seen from Example 1 and Comparative Examples 1 to 3 that zinc oxide whiskers and conductive potassium titanate whiskers can synergistically improve the conductivity of the flash non-woven fabric. The non-conductive potassium titanate whiskers in Comparative Example 6 have little effect on improving the conductivity of the system. In addition, combined with Comparative Example 4, it can be seen that porous silica can cooperate with zinc oxide whiskers and conductive potassium titanate whiskers to significantly improve the conductivity of the system.
[0101] It can be seen from the examples and comparative example 5 that PVA can wet porous silica, zinc oxide whiskers, and conductive potassium titanate whiskers, and cooperate with the compatibilizer to jointly improve the compatibilizer of the system, thereby improving the hydrophobic effect, air permeability, and mechanical properties of the flash-steamed nonwoven fabric.
[0102] It can be seen from Examples 1 to 2 that, compared with graphene, when carbon fiber is used as the conductive agent, the flash-steamed non-woven fabric has better conductivity, mechanical properties and air permeability.
[0103] It can be seen from Examples 1 and 3 to 4 that the mass ratio of zinc oxide whiskers to conductive potassium titanate whiskers can be selected as (1:11):1, and a higher amount of zinc oxide whiskers is selected, the flash-steamed non-woven fabric has better conductivity, and is more beneficial to improving mechanical properties.
[0104] It can be seen from Examples 1 and 5 that the amount of porous silica used in an appropriate range will not only not significantly improve the mechanical properties of the flash-steamed non-woven fabric, but will also significantly contribute to the improvement of conductivity. However, as the amount of porous silica gradually increases, the mechanical properties, air permeability and electrical conductivity of the system show a downward trend. The inventors have found that when the amount of porous silica in the system is greater than or equal to 5 and less than or equal to 15 parts by weight, the mechanical properties, air permeability and electrical conductivity of the flash-steamed non-woven fabric are better.
[0105] It can be seen from Examples 1 and 6 to 8 that the diameter and length of the conductive potassium titanate whiskers have a certain influence on the conductivity of the flash-steamed non-woven fabric. As the diameter and length of the conductive potassium titanate whiskers increase, the conductivity of the flash-steamed non-woven fabric first increases and then decreases. Therefore, it is preferred that the average diameter of the conductive potassium titanate whiskers is greater than or equal to 50 nm and less than or equal to 5 μm, and the average length is greater than or equal to 0.8 μm and less than or equal to 30 μm. It is further preferred that the average diameter is greater than or equal to 0.1 μm and less than or equal to 0.5 μm, and the average length is greater than or equal to 3 μm and less than or equal to 15 μm.
[0106] It can be seen from Examples 1 and 9 to 11 that the average particle size of porous silica has a certain influence on the conductivity of the flash-steamed non-woven fabric. As the average particle size of the porous silica increases, the conductivity of the flash-steamed non-woven fabric first increases and then decreases. The average particle size of the porous silica can be selected to be 10 nm and less than or equal to 3 μm. However, the porous silica with a smaller particle size has a relatively poor effect with the conductive agent, zinc oxide whisker, and conductive potassium titanate whisker. The conductivity of the flash-steamed non-woven fabric with porous silica having an average particle size greater than or equal to 1 μm and less than or equal to 2 μm is better.
[0107] It can be seen from Examples 1 and 12 that, compared with POE-g-MAH compatibilizer, LLDPE-g-MAH has better compatibility with HDPE matrix and other inorganic materials, which makes the mechanical properties and conductive properties of the flash non-woven fabric better.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A conductive flash evaporated sheet, characterized in that: The invention comprises the following components in parts by weight: 100 parts of high-density polyethylene, 4-20 parts of carbon-based conductive agent, 3-10 parts of conductive whiskers, 5-15 parts of porous silicon dioxide, 1-5 parts of polyvinyl alcohol, 1-5 parts of compatibilizer, and 0-2 parts of auxiliary agent; the conductive whiskers include zinc oxide whiskers and conductive potassium titanate whiskers; The resistivity of the conductive flash evaporated sheet is less than or equal to 200 mΩ·cm; The density of the conductive flash-evaporated sheet is greater than or equal to 0.4 g / cm3 and less than or equal to 0.5 g / cm3.
2. The conductive flash vaporized sheet according to claim 1, characterized in that: The average particle size of the porous silica is greater than or equal to 0.01 μm and less than or equal to 3 μm.
3. The conductive flash evaporated sheet according to claim 2, characterized in that: The average particle size of the porous silica is greater than or equal to 1 μm and less than or equal to 2 μm.
4. The conductive flash evaporated sheet according to claim 1, characterized in that: The mass ratio of the zinc oxide whisker to the conductive potassium titanate whisker is (1-12):
1.
5. The conductive flash vaporized sheet according to claim 1, characterized in that: The conductive potassium titanate whiskers have an average diameter greater than or equal to 0.05 μm and less than or equal to 5 μm, and an average length greater than or equal to 0.8 μm and less than or equal to 30 μm.
6. The conductive flash evaporated sheet according to claim 5, characterized in that: The conductive potassium titanate whiskers have an average diameter greater than or equal to 0.1 μm and less than or equal to 0.5 μm, and an average length greater than or equal to 3 μm and less than or equal to 15 μm.
7. The conductive flash evaporated sheet according to claim 1, characterized in that: The conductive potassium titanate whisker is antimony tin oxide modified potassium titanate whisker.
8. The conductive flash evaporated sheet according to claim 1, characterized in that: Include at least one of the following: A. The compatibilizer includes at least one of POE-g-MAH, PE-g-MAH, and LLDPE-g-MAH; B. The carbon-based conductive agent includes at least one of graphene, conductive carbon black, and carbon fiber; C. The average diameter of the zinc oxide whiskers is greater than or equal to 0.5 μm and less than or equal to 5 μm, and the average length is greater than or equal to 10 μm and less than or equal to 50 μm; D. The auxiliary agent includes at least one of an antioxidant, a lubricant, and a flame retardant.
9. A method for preparing a conductive flash evaporated sheet according to any one of claims 1 to 8, characterized in that: The steps include: (1) The raw materials are blended, extruded and granulated to obtain a masterbatch; (2) mixing the masterbatch and the solvent, and then heating and introducing nitrogen so that the temperature in the mixing device is greater than or equal to 200° C. and less than or equal to 230° C., and the pressure is greater than or equal to 10 MPa and less than or equal to 12 MPa, to obtain a spinning solution; (3) The spinning solution is subjected to flash spinning, cold pressing, and hot rolling to obtain the conductive flash sheet.
10. Use of the conductive flash evaporated sheet according to any one of claims 1 to 8 in preparing a gas diffusion layer of a battery.
Citation Information
Patent Citations
Antistatic flash-spun composite nonwoven fabric and preparation method thereof
CN115323628B
HDPE-carbon fiber-zinc oxide crystal whisker conductive composite material and preparation method thereof
CN101565524A
Preparation method of conducting fiber
CN101845679A
Method for manufacturing polyvinyl acetal conductive fibers
CN102978731A
Method for manufacturing conductive polypropylene fibers
CN102978738A